Opportunities for inclusive and efficient low carbon food system development in Bangladesh. (15th October 2021) - Nazmul Islam, K.M.; Sultana, Afrin; Wadley, David; Dargusch, Paul; Henry, Matieu; Naito, Yurie
Abstract: The food system is a significant source of rising greenhouse gas emissions in Bangladesh due to increasing food demand, and ongoing economic growth. The country needs to develop low carbon pathways for the food system that strengthen food security, reduce vulnerability to climate change, and help to achieve the United Nations Sustainable Development Goals. In this paper we analyse the historical trajectory of greenhouse gas emissions of the food system in Bangladesh, and identify various strategies for reducing those emissions. Our analysis reveals that greenhouse gas emissions from Bangladesh's food system doubled from 1990 to 2017, and from the processes included in this study are projected to rise up to 250% by 2050 under a business as usual scenario. Compared with that scenario, a 'National Policy-Based Circular Economy' scenario could achieve a 75% reduction in greenhouse gas emissions in the same period for same level of food supply and production. Major reductions in greenhouse gas emissions could be achieved through activities such as alternative wetting and drying in rice cultivation, and the valorisation of organic waste generated by the food system. Graphical abstract: Image 1 Highlights: Application of macro level LCA for food system in a developing country setting. The carbon footprint from food system projected to rise in Bangladesh by 2.5 times in 2050. Around 75% decarbonization can be achievable under the circular economy based national strategies.